ANALISIS SELISIH BIAYA PRODUKSI SEBAGAI ALAT PENGENDALIAN BIAYA PRODUKSI - Suwandi, Eko Darmawan (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2014)
The calculation of the difference between the cost of production or cost of production deviation calculation is one that aims to management. The calculation is one of the means of controlling production costs. Controlling the cost of production is by comparing the cost of a standard that has been set by the company with its actual cost. From these calculations, the management can determine the cost of parts that deviate both favorable or unfavorable nature and under the control of anyone. Difference in cost of production is profitable if the costs of production standards set larger than the actual production cost. While the difference in the cost of production is not profitable if the costs of production standards set smaller than the actual production cost. Small and Medium Industry"Batik SekarJagad Tanuraksan" is one of the manufacturing company engaged in the production with output in the form of batik cloth. These it are mass produces batik clothin bulk and serve orders from customersin both thelarge and small parties. Therefore thecompanyrequiresthe calculation of the difference in production cost analysis that generates accounting information useful in controlling production costs. Keywords: Production Cost, Analysis ofThe Difference inProductionCost, ProductionCost Control.